FASILITAS PEMBELAJARAN DAN RUANG KOMUNITAS DIGITAL - Henry Halim; Dewi Ratnaningrum (Jurusan Arsitektur dan Perencanaan, 2019)
Today, generation of millennials is a topic that is quite warm among the people, starting from the aspect of education, technology and morals and culture. Millennials or sometimes also called generation Y are a group of people born after Generation X, namely people born in the 1980s and 2000s. Generation of millennials has a characteristic that is, they are very creative in the field of digital technology. Today the development of the creative economy is very rapid. The contribution of the creative economy to the national economy is increasingly evident. The added value generated by the creative economy also increases every year. The growth of the creative economy sector is around 5.76%. This means that it is above the growth of the electricity, gas and clean water sector, mining and quarrying, agriculture, livestock, forestry and fisheries, services and processing industries. Creative Economy is the Pillar of the Nation's Economy. Especially in the field of video blogging, video blogs are mostly asked by generations of millennials and jobs as video blogs, and are also suitable for generations of millennials because of their creative nature and flexible ways of working. The problem is that many generations of millennials are lacking in the knowledge of making interesting content. Thus the Digital Community Learning and Space Facilities project was created which can realize the ideals of the millennials generation that lack creativity in the field. With the method of field survey, shape grammar, and green architecture, this project can be a useful project for the surrounding environment and can be a useful forum for millennials to be able to find and analyze problems that occur in the development of information technology and the development of creative economics in the field of blogs video. Abstrak Dewasa ini, generasi millennials menjadi topik yang cukup hangat di kalangan masyarakat, mulai dari segi pendidikan, teknologi maupun moral dan budaya. Millennials atau kadang juga disebut dengan generasi Y adalah sekelompok orang yang lahir setelah Generasi X, yaitu orang yang lahir pada kisaran tahun 1980- 2000an. Generasi millennials memiliki ciri khas yaitu, mereka sangat kreatif di bidang teknologi digital. Dewasa ini perkembangan terhadap ekonomi kreatif sangatlah pesat. Kontribusi ekonomi kreatif pada perekonomian nasional semakin nyata. Nilai tambah yang dihasilkan ekonomi kreatif juga mengalami peningkatan setiap tahun. Pertumbuhan sektor ekonomi kreatif sekitar 5,76 %. Artinya berada di atas pertumbuhan sektor listrik, gas dan air bersih, pertambangan dan penggalian, pertanian, peternakan, kehutanan dan perikanan, jasa-jasa dan industri pengolahan. Ekonomi Kreatif adalah Pilar Perekonomian Bangsa. Terlebih di bidang Blog video, blog video banyak diminati oleh generasi millennials dan pekerjaan sebagai blog video, dan juga cocok bagi generasi millennials karena sifat mereka yang kreatif dan cara kerja yang bersifat fleksibel. Permasalahannya adalah banyak generasi millennials yang minim dengan ilmu tentang membuat sebuah konten yang menarik. Dengan demikian dibuatlah proyek Fasilitas Pembelajaran Dan Ruang Komunitas Digital yang dapat mewujudkan cita-cita generasi millennials yang minim akan kreatifitas di bidang tersebut. Dengan metode Survey lapangan, shape grammar, dan green architecture, proyek ini dapat menjadi proyek yang berguna bagi lingkungan sekitarnya dan dapat menjadi wadah yang bermanfaat bagi generasi millennials agar mampu menemukan dan menganalisa permasalahan yang terjadi pada perkembangan teknologi informasi dan perkembangan ekonomi kreatif di bidang blog video.